Coronary Artery and Pulmonary Artery Fistula - Khaled Sherif, MD; Haitham Mazek, MD; Mohammad Otahbachi, MD (JACC: Case Reports, 2020)
Coronary artery fistula is a rare condition that can be congenital or acquired. Most patients with these anomalies remain asymptomatic, but symptoms and complications may develop with increasing age. We discuss the clinical presentation, diagnostic work-up, and management options for this condition. (Level of Difficulty: Intermediate.)